The Role of the Church in Responding to the Moral Crisis of the Young Generation in the Digital Era - Siburian, Dame (Cattleya Darmaya Fortuna, 2024)
The rapid development of digital technology has brought significant changes to the lifestyles and mindsets of the younger generation. However, behind this progress, various moral challenges arise, such as individualism, hedonism, behavioral deviations, and a decline in spiritual values. The church, as a spiritual institution, has a crucial responsibility to provide faith and character development for the younger generation so they can face the moral crisis in the digital era. This study aims to analyze the church's role in responding to the phenomenon of moral degradation occurring among Christian youth. The methods used are literature study and a qualitative theological approach by examining various biblical sources, theological writings, and research findings related to digital faith education. The study results indicate that the church needs to update its ministry strategy through strengthening digital communities, spiritual formation relevant to the current context, and collaboration between the church, families, and schools. In conclusion, the church is called to be an agent of moral transformation that presents the love of Christ in the digital world, while instilling strong faith values ​​in the younger generation.